Efectos de la domesticación de los rizobios simbiontes de alfalfa, sobre su capacidad de fijar nitrógeno y degradar óxido nitroso - Brambilla, Silvina Maricel (2020)
The availability of nitrogen is a critical factor for crop productivity. The addition of synthetic nitrogen fertilizers derived from petroleum has partially reduced nitrogen deficiency in many crops. However, the production, distribution and application of these nitrogen fertilizers are costly processes that produce high greenhouse gas emissions, including nitrous oxide (N2O). A sustainable alternative to mitigate the use of nitrogen fertilizers is the cultivation of legumes capable of fixing nitrogen in association with symbiont bacteria in specific organs called nodules. Many legumes, including alfalfa, are not only capable of growing without nitrogen fertilization, but also provide nitrogen to the soil. While legumes play a key role in the sustainability of agriculture, senescent nodules can be a vast source of organic nitrogen that results in high N2O emissions. In this doctoral thesis, the molecular bases that explain the high emission of N2O in alfalfa culture are presented. Specifically, it was found that, during the domestication process, the strains currently used to inoculate alfalfa at the commercial level (Sinorhizobium meliloti B399 and Sinorhizobium meliloti B401) retained their ability to fix nitrogen efficiently, but lost their ability to degrade N2O. This deficiency is due to the deletion of the NOS cluster that codes for the N2O reductase enzyme complex (NOS-). During the screening of new environmentally friendly natural rhizobia containing the NOS cluster (NOS+), the presence of rhizobia containing antibiotic resistance genes in synthetic plasmids was detected. Thus, genomic sequencing of hypothetically natural rhizobia would be necessary to ensure high environmental and public health safety of plant growth promoting bacteria used as commercial inoculants. On the other hand, the bioinfomatic and experimental analysis of new isolates of rhizobia showed that spontaneous mutants of the napC gene arise in nature that combine high nitrogen fixation efficiency with low N2O emission. In addition, a subgroup of these natural strains showed similar nitrogen fixation and nodulation efficiency in relation to commercial strain B399. In this way, the results of this doctoral thesis suggest that it is possible to move towards a sustainable production of alfalfa, both in economic and ecological terms.